2011
DOI: 10.1212/wnl.0b013e318221ad02
|View full text |Cite
|
Sign up to set email alerts
|

Severity of leukoaraiosis determines clinical phenotype after brain infarction

Abstract: Objective: To determine whether the extent of leukoaraiosis, a composite marker of baseline brain integrity, differed between patients with TIA with diffusion-weighted imaging (DWI) evidence of infarction (transient symptoms with infarction [TSI]) and patients with ischemic stroke.Methods: Leukoaraiosis volume on MRI was quantified in a consecutive series of 153 TSI and 354 ischemic stroke patients with comparable infarct volumes on DWI. We explored the relationship between leukoaraiosis volume and clinical ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(36 reference statements)
3
12
0
Order By: Relevance
“…However, the association between leukoaraiosis and recurrent stroke risk cannot be explained solely on the basis of shared risk factors because the present study and previously published studies clearly indicate that leukoaraiosis is a predictor of stroke risk even after controlling for by guest on May 9, 2018 http://stroke.ahajournals.org/ Downloaded from vascular risk factors. 2,13,15,23 Of note, none of the conventional factors except for hypertension that confer an increased risk in the long-term predicted stroke recurrence in the short-term in the present study, consistent with the notion that leukoaraiosis influences short-term risk of recurrent stroke through other mechanisms. Prior studies have suggested that the extent of leukoaraiosis can negatively affect the brain's capacity to tolerate an ischemic insult; among patients with cerebral ischemia, those with extensive leukoaraiosis are more likely to develop completed cerebral infarction, 6 and among patients with acute infarction, those with extensive leukoaraiosis are more likely to develop severe and persistent clinical deficits.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the association between leukoaraiosis and recurrent stroke risk cannot be explained solely on the basis of shared risk factors because the present study and previously published studies clearly indicate that leukoaraiosis is a predictor of stroke risk even after controlling for by guest on May 9, 2018 http://stroke.ahajournals.org/ Downloaded from vascular risk factors. 2,13,15,23 Of note, none of the conventional factors except for hypertension that confer an increased risk in the long-term predicted stroke recurrence in the short-term in the present study, consistent with the notion that leukoaraiosis influences short-term risk of recurrent stroke through other mechanisms. Prior studies have suggested that the extent of leukoaraiosis can negatively affect the brain's capacity to tolerate an ischemic insult; among patients with cerebral ischemia, those with extensive leukoaraiosis are more likely to develop completed cerebral infarction, 6 and among patients with acute infarction, those with extensive leukoaraiosis are more likely to develop severe and persistent clinical deficits.…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies have suggested that the extent of leukoaraiosis can negatively affect the brain's capacity to tolerate an ischemic insult; among patients with cerebral ischemia, those with extensive leukoaraiosis are more likely to develop completed cerebral infarction, 6 and among patients with acute infarction, those with extensive leukoaraiosis are more likely to develop severe and persistent clinical deficits. 1,2 Given that asymptomatic new infarcts are substantially more common, as much as 17× more common-than symptomatic infarcts during the first few days after an ischemic stroke, 24 impaired ability of the brain to tolerate ischemia and its reduced capacity to compensate for the lost function in the presence of extensive leukoaraiosis could potentially facilitate conversion of asymptomatic infarcts into symptomatic infarcts. In support of this view, procedures that are associated with high risk of embolism to the brain, such as carotid artery stenting, 25,26 carotid endarterectomy, 26,27 and total aortic arch replacement, 28 confer a higher perioperative risk of symptomatic stroke in patients with extensive leukoaraiosis when compared with those with less severe leukoaraiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity of LA was assessed using a previously published semi-automated volumetric analysis method with high inter-rater reliability 13. MRI were acquired on 1.5 T Signa scanners (GE Medical Systems, Milwaukee, Wisconsin, USA), and all scans were converted to analyze format using MRIcro software (University of Nottingham School of Psychology, Nottingham, UK, http://www.mricro.com).…”
Section: Methodsmentioning
confidence: 99%
“…MRI were acquired on 1.5 T Signa scanners (GE Medical Systems, Milwaukee, Wisconsin, USA), and all scans were converted to analyze format using MRIcro software (University of Nottingham School of Psychology, Nottingham, UK, http://www.mricro.com). Computer assisted determination of LA volume (LAv) included: (a) creating LA maps using axial T2 fluid attenuated inversion recovery sequences, (b) aligning these maps with the corresponding diffusion weighted imaging (DWI) sequences for exclusion of acute ischemia, edema, and chronic territorial infarcts, and (c) calculating the total LAv by doubling the LAv in the hemisphere unaffected by the stroke and adjusted for head size, as previously described 13. All images in this study were assessed by two investigators (NSR and KF) prospectively, with the sample intraclass correlation coefficient for LAv of 0.97, and blinded to patient CTA characteristics, recanalization status, and clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%